MULTI LEVEL MARKETING (MLM) Sebuah Bisnis ldaman - Nuryasman MN (Jurnal Manajemen, 2008)
Today Network Marketing is famous by Multi Level Marketing begin sharp glance by owner of good to promote their products. If we try to compare between business conversional and Multi Level Marketing we can get some advantages to uses the system of Multi Level Marketing as we can press down cost of promotion until minimize level.For This time many people interest for this business at the first time only as side business but the next they begin to focus. Multi Level Marketing business very flexible inÂ  Financial Capital, with the low cost capital and get the benefit without limit. In the operational of this business is very simple and the risk is very insignificant and carry out a plan in Domestic and International Business.Until today only some of people know about MLM business and the fact the have a certain view Negative about it. This written try to give comprehension about MLM business.Â  how to operate, how to control and how to get successes in this business.